French cities’ struggle against incivilities: from theory to practices in regulating urban public space - Gayet-Viaud, Carole (European journal on criminal policy and research, 2017)
In France, public policies began defining “incivilities” as a primary topic and target to focus on more than two decades ago. Yet what this term actually means is still somewhat unclear: almost every organization that uses it has its own definition, sometimes its own observatory. Despite, or perhaps because of, its very vagueness, the concept has become widely shared and used, securing itself a place on the agendas of most local security policies, becoming an explicit part of the remits of an increasing number of professionals, from police officers to social workers, including a wide range of municipal agents. The range of situations and behaviors potentially included in the list of “unruly conduct” is seemingly endless, from groups of teenagers hanging out to homeless people privatizing public places, and from using playgrounds as public toilets to noise, garbage, dog fouling, graffiti, queue-jumping, pushing and shoving, street harassment, insults of all kinds, badly parked cars, and so forth. However, not all of them provoke the same public attention. This article focuses on the way disorders are actually defined, measured, and dealt with in practice. Incivilities are often said to be growing because of increasing powerlessness. Our research proves action is far from being merely correlative to the legal capacity for sanction.